2020
DOI: 10.1002/2211-5463.13065
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of the 67‐kDa isoform of glutamate decarboxylase alters conditioned fear behavior in rats

Abstract: The GABAergic system is thought to play an important role in the control of cognition and emotion, such as fear, and is related to the pathophysiology of psychiatric disorders. For example, the expression of the 67-kDa isoform of glutamate decarboxylase (GAD67), a GABA-producing enzyme, is downregulated in the postmortem brains of patients with major depressive disorder and schizophrenia. However, knocking out the Gad1 gene, which encodes GAD67, is lethal in mice, and thus, the association between Gad1 and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…Third, we also observed a slight delay in fear extinction in the HET group. This result is similar to the findings of previous studies in amygdalaspecific Gad1 knockdown mice (Heldt et al, 2012), PV neuronspecific Gad1 knockdown mice (Brown et al, 2015), and Gad1 −/− rats (Fujihara et al, 2020b). Considering that amygdala-specific knockdown is sufficient to cause this phenotype, the reduction of GAD67 and subsequent impairment in GABAergic transmission in the amygdala may be responsible for this behavior in HET rats as well.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Third, we also observed a slight delay in fear extinction in the HET group. This result is similar to the findings of previous studies in amygdalaspecific Gad1 knockdown mice (Heldt et al, 2012), PV neuronspecific Gad1 knockdown mice (Brown et al, 2015), and Gad1 −/− rats (Fujihara et al, 2020b). Considering that amygdala-specific knockdown is sufficient to cause this phenotype, the reduction of GAD67 and subsequent impairment in GABAergic transmission in the amygdala may be responsible for this behavior in HET rats as well.…”
Section: Discussionsupporting
confidence: 91%
“…Seven days after the last injection of MK-801, we started the behavioral test battery. The acoustic startle response (including a prepulse inhibition [PPI]), Y-maze, elevated plus-maze, open field, social interaction, forced swim, and fear conditioning tests were conducted as described previously with minor modifications (Fujihara et al, 2015a;Miyata et al, 2019;Fujihara et al, 2020a, Fujihara et al, 2020b. The test battery was performed in the above-mentioned order (see Supplementary Table S1).…”
Section: Behavioral Analysismentioning
confidence: 99%
“…However, a selective ablation of GAD67 in somatostatin interneurons has been shown to enhance anxiety like behavior ( Miyata et al, 2019 ). Moreover, a recent study in GAD67 knock out rats has also demonstrated enhancement of contextual fear memory ( Fujihara et al, 2021 ). We propose these gene-dosage -dependent and isozyme-specific effects to be related to a differential role of GAD65 and GAD67 in the dDG and vDG during stressful experiences.…”
Section: Introductionmentioning
confidence: 99%
“…These authors showed that chronic stress induced (GAD65) mRNA expression whereas acute stress selectively increased (GAD67) mRNA in the hypothalamus and hippocampus. In a recent study, it was also shown that the loss of (Gad67) function, altered conditioned fear behavior in adult rats (Fujihara et al 2020). As we were assessing an acute anxiety model, we evaluated the effect of salicylic acid on (GAD 67) but not (GAD65) expression.…”
Section: Discussionmentioning
confidence: 96%